Emotional Threat Perception and Its Association with Neurocognition in Social Anxiety Disorder. Issue 6 (November 2022) - Mathai, Anjali Thomas; Rai, Shweta; Behere, Rishikesh V.
Background: The negative appraisal of emotional stimuli is a feature of social anxiety disorder (SAD). People with SAD demonstrate deficits in neurocognitive performance while performing tasks of attention. However, the relationship between attentional control, working memory, and threat perception in SAD has not been studied well. The present study aimed to identify patterns of threat perception in relation to performance on attention and visuospatial working memory tasks in individuals with SAD. Methods: Subjects with SAD ( n = 27) and a healthy comparative (HC) group ( n = 26) completed tasks of sustained and focused attention, visuospatial working memory, computerized emotion identification, and pictorial emotional Stroop. Results: The SAD group had decreased performance in the domains of sustained (P = 0.001) and focused attention (P = 0.04). They also had an enhanced threat perception as demonstrated by greater reaction time to anger (P = 0.03), lower emotion recognition accuracy (P = 0.05), and higher over-identification of the threat to neutral and nonthreatening faces. However, the Stroop effect was not demonstrated across the groups. No group difference was seen in the performance on the visuospatial working memory tasks. Lower focused attention was significantly correlated with higher emotional threat perception (ETP; P = 0.001) in the SAD group. Conclusion: People with SAD have greater deficits in attention processing and ETP. The attention deficits were associated with enhanced ETP in social anxiety. The link between threat perception and cognitive functions would aid in a better understanding of SAD and in planning appropriate intervention.